A területi politika irányítási összefüggései - Pálné Kovács, Ilona (Tér és Társadalom, 1992)
The elaboration of the Hungarian regional development model is on a forced track. At present, there are certain realities one cannot neglect, though there is still free choice in many respects, as well. It would not make any sense to question that the government will have a special role in regional development for a long time also in the future. This special role, on the one hand, is justified by the extent of regional differences, the appearance of the zones of crisis. On the other hand, the justification originates from the lack of those autonomous organizations and strata which could substitute the government. These organizations are lacking in income, property and ownership, and legal aspects as well. At the same time, the economy, the social policy and the organizations of supply are characterized by the overwhelming role of the government. Until these characteristics disappear, the management, financing, and the means of regional development will also have the characteristics of nationalized organizations. Though the processes of privatization, marketization, local governments and civil organizations, that can reduce the role of the government, have already started, their operation they are not strong enough to counterbalance the influence of the government. Consequently, the strategy of regional development is a government strategy, which aims at minimizing the role of the government. It is very important to emphasize that the degree of nationalization in regional development, and the degree of decentralization are two different issues. Though the two are closely interrelated, they cannot be mixed. When the necessity of the decentralization of regional development is emphasized, two different requreiments are worded at the same time; One of them is the requirement to decentralize the decision-making process of regional development, and the other is to make it more democratic. Due to its structure and character, the local authorities are capable of meeting these needs. As opposed to this, the regional development policy of the government is centralized and administrative. Whenever the transitional predominance of government role is emphasized it means the following: as the local authorities cannot be the prime, or exclusive actors of regional development due to their actual conditions, the government cannot get rid of its obligations in the field of regional development and regional equalization with the simple declaration of the freedom of local authorities. In other words: the aim of government regional development is nothing else, but the continuous liquidation of its own reason for existence, as the final product of central regional development is the creation of regional units capable of independence. In summary: the precondition of an innovation-oriented, progressive model of regional development based on local resources is decentralized management. A development model, that aims at institutionalizing the partnership between the government and the local authorities also requires decentralized power, political and distributional structures. However, a great many factors act against decentralization at present. In the first place, it is the readiness and capability of the government to centralize that act against decentralization. Nevertheless, the numerous decentralized organizations in the field are also great obstacles before the local authorities in the fulfilment of their actual roles. Besides many other requirements, gradual reform and significant political decentralization of administration is the most important precondition for the introduction of a progressive model of regional policy.